Analysis of the Association between Stunting and Saliva Potential of Hydrogen (pH) in Preschool Children - Dian Fitri Ana Dewi; Silvia Prasetyowati; Siti Fitria Ulfah; Anshad Ansari (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Stunting can affect dental health due to changes in saliva content. Saliva that cannot work optimally will increase the risk of dental caries. The problem in this research is the high level of caries in preschool children at the DWP V Jatirejo Kindergarten. This study aims to determine the association between stunting and the potential of hydrogen (pH) in the saliva of preschool children at DWP V Jatirejo Kindergarten, Lekok District, Pasuruan Regency. The study design was an analytic observational with a cross-sectional approach, the sample in this study was 40 students who were determined using the Slovin formula with a proportional stratified random sampling technique. The stunting variable data collection method was measuring of Height/Age using microtoise and the saliva pH variable was measured using pH meters, and the data analysis techniques used the chi-squared test. Results: There is an association between stunting and the saliva pH in preschool children at DWP V Jatirejo Kindergarten. The Height/Age measurement results to determine the stunting status of respondents were found to be dominated by short height (stunted), and the saliva pH category of respondents was dominated by the acidic category.